SUBSTANTIATION OF APPLICATION OF ALLOGENIC FIBROBLASTS IN TREATMENT OF EXTENSIVE BURNS - E. Ya. Fistal’; V. V. Soloshenko (Вестник хирургии имени И.И. Грекова)
Recent researches left no doubt in clinical efficacy of allogenic fibroblasts transplantation in case of burn treatment. There are several problems concerning indications and terms of transplantation performance of cell culture in treatment of boundary burns. The authors would like to prove an application of allogenic fibroblast culture in surgical treatment of victims with extensive dermal burns. The authors analyzed the results of surgical treatment of 36 miners, who were cured in burn department of V.K. Gusak Institute of Emergency and Plastic Surgery (Donetsk) at the period from 2004 to 2013. It was found that the application of fetal allogenic fibroblasts reduced the number of repeated autoplasty on 36% in main group of patients due to optimization of wound healing in case of burns.